Corporate social responsibility and firms' performance: A stratigraphical analysis - Nicola Comincioli; Laura Poddi; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2012)
Over the last two decades in OECD countries an increasing number of firms are obtaining certification as Socially Responsible (CSR is the acronym for Corporate Social Responsibility). Several studies (including Preston and O'Bannon, 1997; Waddock and Graves, 1997; McWilliams and Sieger, 2001; Ullman, 1985) have sought to test whether there is a relation between Social Responsibility certification and the firms' performance. Our work builds a CSR index that intersects two of the three main international indices (Domini 400 Social Index, Dow Jones Sustainability World Index, FTSE4Good Index), in order to overcome some problems related to the multiplicity of CSR definitions and certifications. By using this database, our work carries out a stratigraphical analysis in order to verify whether some variables are statistically different in the CSR group with respect to the benchmark case (non-CSR). The main results show that there are several interesting differences in some economic indicators between CSR and non-CSR firms and between USA and EU, and among different industrial sectors.
Keywords: M14; C23; O10; 330; Corporate Social Responsibility; Growth